Antimalarial activity and mechanisms of action of two novel 4-aminoquinolines against chloroquine-resistant parasites - Aguiar, Anna Caroline Campos (2012)
Fundação Oswaldo Cruz. Centro de Pesquisas Rene Rachou. Belo Horizonte, MG Brazil/Universidade Federal de Minas Gerais. Faculdade de Medicina. Programa de Pos Graduação em Medicina Molecular. Belo Horizonte, MG, Brazil